2019
DOI: 10.1007/s11096-019-00816-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical pharmacy practice in the care of Chronic Kidney Disease patients: a systematic review

Abstract: Background Clinical pharmacy services have potential to contribute significantly to the multidisciplinary team providing safe, effective and economic care for patients. Given recent practice developments (e.g. polypharmacy reviews and pharmacist prescribing) there is a need to provide a current synthesis of the evidence base for characteristics and outcomes of clinical pharmacy practice in chronic kidney disease patients. Aim of the review To critically appraise, synthesise an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 69 publications
1
80
1
1
Order By: Relevance
“…According to a systematic review (Raiisi et al, 2019) of clinical pharmacy practice in the care of chronic kidney disease patients, various pharmacist activities in different studies included modifying drug doses, requesting and monitoring laboratory parameters, assessing the appropriateness of medications, performing medication reconciliation, patient medication counseling, and adherence motivation, and managing speci ic CKD complications. In our study, some of the activities like drug dose modi ications, patient medication counseling and monitoring laboratory parameters were done by the pharmacist.…”
Section: Resultsmentioning
confidence: 99%
“…According to a systematic review (Raiisi et al, 2019) of clinical pharmacy practice in the care of chronic kidney disease patients, various pharmacist activities in different studies included modifying drug doses, requesting and monitoring laboratory parameters, assessing the appropriateness of medications, performing medication reconciliation, patient medication counseling, and adherence motivation, and managing speci ic CKD complications. In our study, some of the activities like drug dose modi ications, patient medication counseling and monitoring laboratory parameters were done by the pharmacist.…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggest that involving pharmacists in the care of patients with CKD improves prescribing practices [ 10 ]. However, most studies have focused on prescribing in the acute care hospital setting or hemodialysis population, or have involved recommendations from a community pharmacist and have not examined the impact of pharmacists as part of the ambulatory kidney care team [ 10 , 14 16 ]. With this in mind, we conducted a retrospective cohort study to examine potentially inappropriate prescribing in older patients with advanced CKD followed in multidisciplinary kidney clinics and examined if inappropriate prescribing was reduced following the introduction of pharmacists into the kidney clinics.…”
Section: Introductionmentioning
confidence: 99%
“… This list is not inclusive of all studies of pharmacist‐based care in patients with kidney disease, which is beyond the scope of this opinion paper. Refer to systematic reviews of this topic by Raiisi and colleagues and Salgado and colleagues 44,45 …”
Section: Opportunities For Pharmacists To Integrate Into the Care Of mentioning
confidence: 99%
“…In patients with kidney diseases, clinical pharmacists' interventions reduced hospital admissions, length of hospital stay, and incidence of ESKD or death 44 . A more recent systematic review demonstrated pharmacist services continue to positively impact disease state management (anemia, blood pressure, and mineral bone disorder) with increasing focus on MTP identification, improvement in health‐related quality of life, patient satisfaction, and cost savings 45 . Studies evaluating multidisciplinary teams with pharmacists vs nephrologist care alone in patients with CKD have demonstrated decreased hospitalizations and mortality 17 .…”
Section: Opportunities For Pharmacists To Integrate Into the Care Of mentioning
confidence: 99%